The policing machine: enforcement, endorsements, and the illusion of public input - Cheng, Tony (The University of Chicago Press, 2024)
"The past few years have seen Americans express passionate demands for police transformation. But even as discussion of no-knock warrants, chokeholds, and body cameras has exploded, any changes to police procedures have only led to the same outcomes. Despite calls for increased accountability, police departments have successfully stonewalled change. In The Policing Machine, Tony Cheng reveals the stages of that resistance, offering a close look at the deep engagement strategies that NYPD precincts have developed with only subsets of the community in order to counter any truly meaningful, democratic oversight. Cheng spent nearly two years in an unprecedented effort to understand the who and how of police-community relationship building in New York City, documenting the many ways the police strategically distributed power and privilege within the community to increase their own public legitimacy without sacrificing their organizational independence. By setting up community councils that are conveniently run by police allies, handing out favors to local churches that will promote the police to their parishioners, and offering additional support to institutions friendly to the police, the NYPD, like police departments all over the country, cultivates political capital through a strategic politics that involves distributing public resources, offering regulatory leniency, and deploying coercive force. The fundamental challenge with police-community relationships, Cheng shows, is not to build them. It is that they already exist and are motivated by a machinery designed to stymie reform"--